The prognostic value of the lactate/albumin ratio for predicting mortality in septic patients presenting to the emergency department: a prospective study. (1st January 2021) - Bou Chebl, Ralphe; Geha, Mirabelle; Assaf, Mohamad; Kattouf, Nadim; Haidar, Saadeddine; Abdeldaem, Karim; Halawi, Nour; Khamis, Mohamed; Makki, Maha; Tamim, Hani; Abou Dagher, Gilbert
Abstract: Objectives: Lactate/albumin (L/A) ratio is a biomarker in sepsis that has been shown to outperform lactate. This prospective study aims to validate the superior prognostic value of the L/A ratio to lactate in sepsis and septic shock. Methods: Prospective cohort conducted from September 2018 till February 2021 on adult patients presenting to the Emergency Department (ED) at a tertiary care centre with sepsis or septic shock. The primary outcome was the prognostic value of the L/A ratio compared to lactate with regards to mortality. Results: A total of 939 septic patients were included throughout the study period. A total of 236 patients developed septic shock. The AUC value of the L/A ratio in septic patients was 0.65 (95% CI 0.61–0.70) and was higher than that of lactate alone 0.60 (95% CI 0.55–0.64) with a p  < .0001. The optimal L/A ratio cut-off threshold that separated survivors from non-survivors was found to be 0.115 for all septic patients. The AUC of the L/A ratio was significantly higher for patients with a lactate ≥2 mmol/L: 0.69 (95% CI 0.64–0.74) versus 0.60 (95% CI 0.54–0.66) with a p  < .0001 as well as for patients with an albumin level less than 30 g/L (AUC = 0.69 95% CI= 0.62–0.75 vs AUC= 0.66 95% CI= 0.59–0.73, p  = .04). Among septic shock patients there was no statically significant difference in the AUC value of the L/A ratio compared to lactate (0.53 95% CI 0.45–0.61 vs 0.50 95% CI 0.43–0.58 respectively with a p -value = .11). Conclusions: The L/A ratio is a better predictor of in-patient mortality than lactate in sepsis patients. This superiority was not found in the septic shock subgroup. Our results encourage the use of the ratio early in the ED as a superior prognostic tool in sepsis patients. Key messages: We aimed to assess the prognostic usefulness of the Lactate/Albumin ratio compared to lactate alone in septic and septic shock patients. The L/A ratio proved to be a better predictor of in-patient mortality than lactate alone in sepsis patients. This pattern also applies across various subgroups in our study (malignancy, diabetics, age above 65, lactate level less than 2 mmol/L, albumin less than 30 g/L). Our results favour the use of the L/A ratio over lactate alone in patients with sepsis and the previously mentioned subgroups. Our results do not favour the use of the ratio instead of lactate in septic shock patients as there was no statistically significant difference between the AUCs of the ratio and lactate alone.